2020
DOI: 10.3390/genes11080910
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis Shows That Most RHDV GI.1 Strains Circulating Since the Late 1990s in France and Sweden Were Recombinant GI.3P–GI.1d Strains

Abstract: Recombination is one of the major sources of genetic variation in viruses. RNA viruses, such as rabbit hemorrhagic disease virus (RHDV), are among the viruses with the highest recombination rates. Several recombination events have been described for RHDV, mostly as a consequence of their genomic architecture. Here, we undertook phylogenetic and recombination analyses of French and Swedish RHDV strains from 1994 to 2016 and uncovered a new intergenotypic recombination event. This event occurred in the late 1990… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 59 publications
2
29
0
Order By: Relevance
“…The 00-21 strain belongs to the GI.1d variant group according to the proposal for a unified classification system for lagoviruses [9]. Complete or almost complete GI.1d genome sequences (without complete UTR sequences) from Bahrain in 2001 and from European countries collected until 2004 have been already obtained [11,18,19], but not from France where this variant has circulated since 1990 [10,12]. The present study characterised the complete genome sequence of a GI.1d strain collected in France in 2000.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 00-21 strain belongs to the GI.1d variant group according to the proposal for a unified classification system for lagoviruses [9]. Complete or almost complete GI.1d genome sequences (without complete UTR sequences) from Bahrain in 2001 and from European countries collected until 2004 have been already obtained [11,18,19], but not from France where this variant has circulated since 1990 [10,12]. The present study characterised the complete genome sequence of a GI.1d strain collected in France in 2000.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, except in the Iberian Peninsula where GI.1b persisted, these two variants were replaced by a new variant GI.1d [10,11]. After the emergence of GI.2, GI.1d strains became a minority but continued to be occasionally identified in France [12]. GII contains pathogenic (EBHSV) and non-pathogenic viruses (hare calicivirus (HaCV)) related to EBHSV [9].…”
mentioning
confidence: 99%
“…Genetic diversity among pathogenic RHDV isolates has been the subject of intense study with the capsid protein (partial or complete) being the main target. Recent advances in sequencing techniques has allowed full genome analysis in Viral Disease in Lagomorphs: A Molecular Perspective DOI: http://dx.doi.org/10.5772/intechopen.98272 retrospective studies and demonstrate the importance of analysing complete genomes [187,188].…”
Section: Evolution: Genotypes Antigenic Variantsmentioning
confidence: 99%
“…In 2017, Nanbu/China/2011 isolates were found in China with a recombination event between the G2 and G6 strains (BoHu et al, 2016). The study reported that phylogenetic and recombination analyses of French and Swedish RHDV strains from 1994 to 2016 revealed that most of the prevalent RHDV G .1 strains were recombinant G .3P-G .1d strains (JoanaAbrantes et al, 2020). Researchers reveal recombination between RHDV (G .2) and EBHSV (G .1) in response to whole-genome sequencing of German rabbit haemorrhagic disease virus (JoanaAbrantes et al, 2020).…”
mentioning
confidence: 99%
“…The study reported that phylogenetic and recombination analyses of French and Swedish RHDV strains from 1994 to 2016 revealed that most of the prevalent RHDV G .1 strains were recombinant G .3P-G .1d strains (JoanaAbrantes et al, 2020). Researchers reveal recombination between RHDV (G .2) and EBHSV (G .1) in response to whole-genome sequencing of German rabbit haemorrhagic disease virus (JoanaAbrantes et al, 2020). Research has found that, Spillover events of RHDV2 (recombinant G .4P-G .2) from Lagomorpha to Eurasian badger (Abade dos Santos et al, 2021).…”
mentioning
confidence: 99%